Tracing Volatiles, Halogens, and Chalcophile Metals during Melt Evolution at the Tolbachik Monogenetic Field, Kamchatka. (26th August 2022) - Iveson, Alexander A; Humphreys, Madeleine C S; Jenner, Frances E; Kunz, Barbara E; Savov, Ivan P; De Hoog, Jan C M; Churikova, Tatiana G; Gordeychik, Boris N; Hammond, Samantha J; Plechov, Pavel Yu; Blundy, Jon; Agostini, Samuele
Abstract: Melt storage and supply beneath arc volcanoes may be distributed between a central stratovolcano and wider fields of monogenetic cones, indicating complex shallow plumbing systems. However, the impact of such spatially variable magma storage conditions on volatile degassing and trace element geochemistry is unclear. This study explores magma generation and storage processes beneath the Tolbachik volcanic field, Kamchatka, Russia, in order to investigate the evolution of the magmatic volatile phase and, specifically, the strong enrichment of chalcophile metals (in particular, Cu) in this system. We present new geochemical data for a large suite of olivine- and clinopyroxene-hosted melt inclusions (and host phenocrysts) from five separate monogenetic cones within the Tolbachik volcanic field. These high-Al composition magmas likely reflect the homogenised fractionation products of primitive intermediate-Mg melt compositions, stored at shallow depths after significant fractional crystallisation. Boron isotope compositions and incompatible trace element ratios of the melt inclusions suggest a deeper plumbing system that is dominated by extensive fractional crystallisation and fed by melts derived from an isotopically homogeneous parental magma composition. Volatile components (H2 O, CO2, S, Cl, F) show that magmas feeding different monogenetic cones had variable initial volatile contents and subsequently experienced different fluid-saturated storage conditions and degassing histories. We also show that melts supplying the Tolbachik volcanic field are strongly enriched in Cu compared with almost all other Kamchatka rocks, including samples from the Tolbachik central stratocones, and other volcanoes situated in close proximity in the Central Kamchatka Depression. The melt inclusions record Cu concentrations ≥450 μg/g at ca . 4–5 wt.% MgO, which can only be explained by bulk incompatible partitioning behaviour of Cu, i.e. evolution under sulphide-undersaturated conditions. We suggest that initial mantle melting in this region exhausted mantle sulphides, leading to sulphide undersaturated primitive melts. This sulphide-free model for the high-Al cone melts is further supported by S/Se and Cu/Ag values that overlap those of the primitive mantle and MORB array, with bulk rock Cu/Ag ratios also overlapping other with other global arc datasets for magma evolution prior to fractionation of a monosulfide solid solution. We therefore demonstrate that the combination of novel chalcophile metal analyses with trace element, isotopic, and volatile data is a powerful tool for deciphering complex magmatic evolution conditions across the entire volcanic field.